Global, regional, and national burden of stroke attributable to diet high in sodium from 1990 to 2019: a systematic analysis from the global burden of disease study 2019 - Zhang, Xuan; Ye, Wen-qian; Xin, Xue-Ke; Gao, Ying-jie; Yang, Fan (Frontiers in Neurology, 2024)
Purpose Given the increasing occurrence of stroke and high-sodium diets (DHIS) over the past 30 years, it is crucial to assess the global, national, and regional impact of DHIS on the burden of stroke. Methods and materials The Global Burden of Diseases Study 2019 provided the study's data. We used the Bayesian meta-regression tool DisMod-MR 2.1 to evaluate the burden of stroke attributable to DHIS. Age-standardized disability-adjusted life years (ASDR) and age-standardized mortality rate (ASMR) were used to quantify the burden. We perform correlation analysis utilizing the Spearman rank-order correlation method, and we calculate the estimated annual percentage change (EAPC) to evaluate temporal trends. Results Globally, DHIS accounts for 17,673.33 thousand disability-adjusted life years (DALYs) and 700.98 thousand deaths of stroke in 2019. The burden of stroke attributable to DHIS has declined between 1990 and 2019 globally and in the majority of regions, with the largest declines seen in regions with high sociodemographic indexes (SDI). Both ASMR and ASDR were higher regionally in regions with moderate SDI than those in developed regions. Furthermore, the absolute values of EAPC, reflecting the rate of decrease, were notably lower in these regions compared to developed nations. High-income North America, categorized within the SDI regions, notably witnessed the smallest decline in ASDR over the last three decades. Additionally, from 1990 to 2019, males consistently bore a larger burden of stroke attributable to DHIS. Conclusion The burden of stroke attributable to DHIS remained a major concern despite advancements in public knowledge of stroke and their utilization of emergency medical services. Over the past 30 years, more burden has been placed on males and regions with moderate SDI values; in males, higher EAPC values for both ASMR and ASDR have been found. This underscores the urgent need for effective interventions to alleviate the burden of stroke associated with DHIS.